A Note on Proline Content in Eucalyptus Hybrid Leaves - Pokhriyal, T. C.; Raturi, A. S. (Indian Forester, 1985)
Accumulation of proline , a free amino acid is a common feature in some of the stress affected crop plants. An attemp was made to study the changes in the proline contents of diffferent leaflets of Eucalyptus hybrid. Maximum (608.77 Î¼g/g dry wt.) and minimum (24.81 Î¼g/g fr.wt.) proline cantents was estimated in the first and tenth leaf blades respectively. But the total proline per leaf blade was highest in the fourth and lowest in the first leaf blade.